2007
DOI: 10.1529/biophysj.106.097360
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Outer Mouth Structure of the hERG Channel with Peptide Toxin Footprinting and Molecular Modeling

Abstract: Previous studies have shown that the unusually long S5-P linker lining human ether a-go-go related gene's (hERG's) outer vestibule is critical for its channel function: point mutations at high-impact positions here can interfere with the inactivation process and, in many cases, also reduce the pore's K+ selectivity. Because no data are available on the equivalent region in the available K channel crystal structures to allow for homology modeling, we used alternative approaches to model its three-dimensional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
119
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 52 publications
(81 reference statements)
2
119
1
Order By: Relevance
“…47,49 Using an early molecular model of Shaker by Durrell and Guy 312 and the results from their mutant cycle analysis, this group then generated a molecular model of the S5-P-S6 region of the K V 1.3 channel. 47 In collaboration with Raymond Norton's group in Melbourne, KTX was manually docked in this model by guiding Lys 27 into the pore such that it would lie near the selectivity filter, and the toxin was then rotated about the central pore axis until Arg 24 in the toxin aligned with Asp p38 (386) in K V 1.3 in a salt bridge suggested by the mutagenesis. 47 Using highresolution solid-state NMR spectroscopy, Lange et al demonstrated that high-affinity binding of KTX to a chimeric KcsA-K V 1.3 channel involves structural rearrangements in both molecules.…”
Section: Peptidic K V 13 Blockersmentioning
confidence: 99%
“…47,49 Using an early molecular model of Shaker by Durrell and Guy 312 and the results from their mutant cycle analysis, this group then generated a molecular model of the S5-P-S6 region of the K V 1.3 channel. 47 In collaboration with Raymond Norton's group in Melbourne, KTX was manually docked in this model by guiding Lys 27 into the pore such that it would lie near the selectivity filter, and the toxin was then rotated about the central pore axis until Arg 24 in the toxin aligned with Asp p38 (386) in K V 1.3 in a salt bridge suggested by the mutagenesis. 47 Using highresolution solid-state NMR spectroscopy, Lange et al demonstrated that high-affinity binding of KTX to a chimeric KcsA-K V 1.3 channel involves structural rearrangements in both molecules.…”
Section: Peptidic K V 13 Blockersmentioning
confidence: 99%
“…1A) (Korolkova et al, 2002). BeKm-1 does not totally occlude ion flux through the hERG pore (Zhang et al, 2003), probably because it binds above the selectivity filter (Tseng et al, 2007).…”
mentioning
confidence: 98%
“…Several such peptide toxins have been identified (Gurrola et al, 1999;Korolkova et al, 2001;Corona et al, 2002;Nastainczyk et al, 2002;Huys et al, 2004). Two peptide toxins purified from scorpions, BeKm-1 and CnErg1 (also called ErgTx1), are the best-studied cases (Korolkova et al, 2002;Pardo-López et al, 2002a,b;Zhang et al, 2003;Tseng et al, 2007). Both toxins bind to hERG's outer vestibule to suppress ion conduction through the pore.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence alignment of KcsA, KvAP, and hERG was generated by T-Coffee [93] and then manually adjusted to increase the accuracy of homology modeling. Although an extracellular loop between S5 and pore helix (between positions 572 and 610) is proposed to be structured and involved in ion conduction in hERG [94], this loop was omitted for simplicity. After the refinement of the structure by molecular mechanics, the model had no dihedral angle violation in the Ramachandran plot, with the exception of distal termini …”
Section: A Inanobe Et Almentioning
confidence: 99%